Teaching polyhedra to eighth-grade junior high school students using the hypnoteaching method assisted by audio-visual media - Sipa'i, Shintia; Putra, Didik Adi; Rohaeti, Euis Eti (Pi Radian: Journal of Mathematics Education, 2025)
This study explores the challenges faced by teachers in implementing online learning, the instructional process and learning scenarios, as well as teacher and student responses, and the learning difficulties experienced by eighth-grade students in understanding polyhedra three-dimensional geometric figures with flat surfaces through the hypnoteaching method assisted by audiovisual media. The participants consisted of 23 eighth-grade students from SMP Mahardika Batujajar, West Bandung Regency. Using a qualitative descriptive design, data were collected through written tests, closed-ended questionnaires, student interviews, and teacher interview guidelines. The written test consisted of six essay questions, while the questionnaire included 24 statements, and interviews and observations were conducted to obtain deeper insights. The findings indicated that teachers encountered several obstacles, mainly limited digital learning facilities, inadequate infrastructure, and unstable internet connectivity. Learning activities were delivered through platforms such as WhatsApp, Google Classroom, Zoom, and Google Forms, supported by lesson plans adapted to the hypnoteaching method. Teacher responses toward the implementation were highly positive, with an average score of 85.69%, while student responses revealed 61.32% positive and 38.68% negative statements, categorized as moderately favorable. Students experienced the greatest difficulty in question six, which required higher-order thinking and the application of formulas related to polyhedra. The average student score was 68.8%, classified as moderately good.